Preventive dental visiting: a critical interpretive synthesis of theory explaining how inequalities arise. Issue 2 (6th December 2016) - Harris, Rebecca V.; Pennington, Andrew; Whitehead, Margaret
Abstract: Background: In many countries, those with lower socioeconomic status are disproportionately affected by poor oral health. This can be attributed, at least in part, to differences in preventive dental visiting. While several theories have been applied to the area, they generally fail to capture the recursive nature of dental visiting behaviour, and fall short of informing the design of complex interventions to tackle inequalities. Objective: To undertake a systematic review and synthesis of theory in order to provide an overview of the pathways which bring about socioeconomic inequalities in early dental visiting, and identify possible intervention points. Methods: Electronic searching identified 8947 titles and abstracts. Paper screening and citation snowballing left 77 included papers. Drawing on the tenets of Critical Interpretive Synthesis, data extraction involved capturing concepts and relationships and translating these sometimes into synthetic constructs. Results: We theorize that at the individual (micro‐level), dental visiting behaviour is influenced by: the ' Importance of obtaining care', ' Emotional response ' and ' Perceived control ', which feed into a balancing of ' Competing Demands ' against ' Internal resources' (coping, self‐identity), although attendance is tempered by the effective ' Affordability and Availability of services' . Positive Care experiences are theorized to lower the demands and increase internal resources associated with dental visiting. We also outline meso‐level factors ' Social norms and sanctions', 'Obligations, expectations and trust', 'Information channels', 'Social structures ' and theorize how these can exert an overwhelming influence in deprived areas. Conclusions: Socioeconomic inequalities in early dental visiting emerge from several stages in the care‐seeking process. Dental visiting behaviour should be viewed not just as a one‐off event, but extending over time and social space. Since there is recursivity in peoples' most recent dental experience any future visits we identify that interventions which make care a positive experience for low socioeconomic patients may be particularly beneficial in reducing inequalities.